Marketing and Controlling in Strategic Forecasting of Innovative Industrial Development - Kuzmynchuk, Nataliia; Kutsenko, Tetiana; Aloshyn, Serhii; Marchenko, Vitalii (Dr. Viktor Koval, 2025)
Introduction. Outlining the strategic vision of alternatives regarding the innovation development of industrial enterprises implies a multifunctional load on marketing and controlling support systems aimed at increasing the effectiveness of managerial influence to ensure the long-term sustainability and competitiveness of enterprises. Marketing and controlling support decision-making in developing the innovation potential of industrial enterprises to ensure their competitiveness in recovering and strengthening the national economy. Aim and tasks. This study aims to develop and substantiate approaches to strategic forecasting regarding the innovation development of industrial enterprises in marketing and controlling support to modernise and accelerate national economy recovery. Results. The study uses an economic and mathematical model to forecast industrial competitiveness by adjusting key innovation potential components. The model reveals that innovation potential depends significantly on prior investments in innovation made in the previous period, which requires sound management decisions regarding the choice of strategic alternatives for innovation development based on marketing and controlling support. An analysis of the forecasted competitiveness of industrial enterprises in 2023-2024 shows that innovative potential has the most significant impact on competitiveness, with R3 parameter equal to 0.5472, which exceeds the value of R2 parameter of 0.1180 for the competitiveness in the previous period. The proposed ADL model with fixed effects for panel data confirms the dependence of industrial competitiveness on innovation. In particular, a conditional increase in innovation potential of 10% leads to a 5.4% increase in the competitiveness of industrial enterprises during the forecast period. Conclusions. Creating a marketing support system for the innovation development of industrial enterprises contributes to the adaptation of industrial enterprises to conditions of rapid technological processes within the industrial paradigm and enhances resilience to external challenges. Controlling makes it possible to optimise processes and increase the efficiency of management decisions to achieve innovation development’s strategic goals and accelerate industrial enterprises’ competitiveness. Analysing strategic alternatives for innovation development based on marketing and controlling enabled the formulation of strategies to increase industrial enterprises’ development innovativeness and effectiveness.